An Austrian Analysis of China's Unsustainable Boom. (27th October 2015) - Howden, David; Li, Jason XingBin
Abstract Austrian Business Cycle Theory can shed light on the ways in which the current Chinese economic boom is unsustainable. On the one hand, government interventions, such as land monopolies, have raised costs for real estate developers. By limiting the availability of investment instruments and access to external markets, government interventions have created a strong demand for housing as a hedging tool. On the other hand, a loose monetary policy and artificially low interest rates have made the property market tempting for developers. Over‐construction and over‐consumption in the housing sector epitomise the capital structure analysis that Austrian economists regard as the core of their business cycle theory.